A Walk in the Woods - Grimes, Nikki; Pinkney, Jerry; Pinkney, J. Brian (New York : Neal Porter Books, Holiday House, 2023)
"A grieving son follows a treasure map his late father left him through the woods they used to explore together."--|cProvided by publisher.
Keywords: Fathers -- Juvenile fiction. -- Death; Fathers and sons -- Juvenile fiction; Grief in children -- Juvenile fiction; Nature -- Juvenile fiction; Forest animals -- Juvenile fiction; Animals -- Juvenile fiction; African American boys -- Juvenile fiction; Fathers -- Fiction. -- Death; Fathers and sons -- Fiction; Grief -- Fiction; Nature -- Fiction; Forest animals -- Fiction; Animals -- Fiction; African Americans -- Fiction; Picture books; Picture books